Nutritional status of pediatric patients with epidermolysis bullosa. A cross-sectional study. : Nutritional status in epidermolysis bullosa. - MORALES-OLVERA, Diana; GRIS-CALVO, Judith I.; GARCÍA-ROMERO, Maria Teresa (Nutrición Clínica y Dietética Hospitalaria, 2022)
Epidermolysis bullosa (EB) is a genetic disorder with continuous formation of blisters and erosions in the skin and mucous membranes as well as multi-systemic involvement. Patients are at high-risk of malnutrition due to decreased food intake and increased nutrient demand. This cross-sectional retrospective study evaluated the daily caloric intake and nutritional status of pediatric patients with EB at a specialized clinic through anthropometric measurements and estimation of the daily intake by 24-hour dietary recall. We used the Waterlow and World Health Organization (WHO) malnutrition classification schemes. Descriptive statistics were used. We included 17 patients with a mean age of 8.4 years (SD 4.6), 82.3% had malnutrition. Those with more severe subtypes, junctional and recessive dystrophic EB, had acute superimposed on chronic malnutrition (100% and 63.4%), wasting (100% and 72.6%), and stunting (0% and 54.4%) more frequently, respectively. Most patients required supplementation (caloric 76.4% and vitamin/mineral 100%). We concluded that there is a high frequency of malnutrition in our EB patients. Although their energy requirements is calculated to be increased in 100-150% of the estimate, our patients only reach 73.1% of that, thus requiring supplementation. Patients with more severe subtypes of EB had chronic malnutrition more frequently. Even though malnutrition is closely linked to wound healing and adequate growth and development of patients, there are few studies about nutrition in EB worldwide. We believe evaluating the nutritional status of these patients is the first step to identifying deficiencies, offering adequate comprehensive medical care and establishing nutritional interventions in a timely manner.